Sealing ability promoted by three different endodontic sealers - Silva, Graziele; Silva, Emmanuel João Nogueira Leal da; Silva, Juliana Melo da; Andrade-Júnior, Carlos Vieira; Ferraz, Caio César Randi (Iranian Endodontic Journal, 2011)
Introduction: The aim of this study was to evaluate the apical and coronal sealing of endodontic fillings promoted by the associations of Sealer 26/Gutta-percha, Endofill/Gutta-percha and Resilon/ Epiphany. Materials and Methods: It was used 38 human canines, 10 teeth for each test group and 4 teeth for each control group. After teeth conventional endodontic treatment, they were immersed in saline solution for thirty days, sealed and stored in India ink for seven days. Then were submitted to a clearing technique and evaluated for infiltration by stereoscopic microscope. The data were statistically analyzed by ANOVA and Bonferroni tests. Results: The results showed no significant differences (p> 0.05) between the three groups of filling materials used. Conclusion: Considering the limitations of this in vitro study, it seems that no material showed superiority related to the ability of apical and coronary sealing.